Insights from a community-based survey on factors influencing acceptance and uptake of Paxlovid (nirmatrelvir and ritonavir) as a COVID-19 antiviral medication in Singapore - Soh, Alexius Matthias Sheng En (2024)
Introduction: Antiviral treatment can reduce the burden of COVID-19. But utilisation can be suboptimal, even in a setting like Singapore where it is fully subsidized for those with selected medical conditions and older adults (≥ 50 years). We hence investigated the factors affecting awareness, acceptance, and initiative to request Paxlovid. Methods: We assessed the Paxlovid awareness, factors impacting its uptake in a survey conducted from August 2022 to September 2022 through the SOCRATES cohort. Multivariable logistic regression was used to investigate associations between sociodemographics, perceptions, and attitudes with the key study outcomes. Results: Among respondents to the Paxlovid survey, 54% were aware of Paxlovid. On being provided essential details about Paxlovid, 75% reported they would likely be receptive to taking it if prescribed, and 38% indicated the initiative to request for it if it was not suggested by their doctors. Factors associated with awareness of Paxlovid include aged 40 years old and above, higher education, citing websites as an information source, greater trust in healthcare providers (aOR: 1.65, 95% CI 1.26 – 2.15) and government communications (aOR: 0.69, 95% CI 0.55 – 0.86), and higher perceived risk of COVID-19 infection (aOR: 1.25, 95% CI 1.10 – 1.42). Factors associated with acceptance to take Paxlovid include male gender, citing trust in healthcare providers (aOR: 1.49, 95% CI 1.11 – 1.99) and government communications (aOR: 1.38, 95% CI 1.09 – 1.76), and higher perceived severity of COVID-19 (aOR: 1.23, 95% CI 1.07 – 1.42). Factors associated with initiative to request Paxlovid include male gender, having pre-existing diabetes and higher perceived severity of COVID-19 (aOR: 1.24, 95% CI 1.09 – 1.40). The most common reasons for why respondents might not take Paxlovid were concerns about side effects (64%), concerns about costs (29%), and the perception that COVID-19 is a mild (25%). Conclusion: The majority of our respondents would take Paxlovid if it was prescribed to them, but a much smaller proportion would have the initiative to request for this. Key factors that may influence uptake are COVID-19 threat perceptions, trust in healthcare and government, and perceptions of the drug’s side effects and cost.